Remarkably stable metal–organic frameworks on an inert substrate: M-TCNQ on graphene (M = Ni, Fe, Mn). Issue 26 (24th June 2022) - Jakub, Zdeněk; Kurowská, Anna; Herich, Ondrej; Černá, Lenka; Kormoš, Lukáš; Shahsavar, Azin; Procházka, Pavel; Čechal, Jan
Abstract : We present three isostructural substrate-decoupled 2D metal organic frameworks, which are stable in ambient environment and can be studied with atomic-scale precision. Abstract : Potential applications of 2D metal–organic frameworks (MOF) require the frameworks to be monophase and well-defined at the atomic scale, to be decoupled from the supporting substrate, and to remain stable at the application conditions. Here, we present three systems meeting this elusive set of requirements: M-TCNQ (M = Ni, Fe, Mn) on epitaxial graphene/Ir(111). We study the systems experimentally by scanning tunneling microscopy, low energy electron microscopy and X-ray photoelectron spectroscopy. When synthesized on graphene, the 2D M-TCNQ MOFs are monophase with M1 (TCNQ)1 stoichiometry, no alternative structure was observed with slight variation of the preparation protocol. We further demonstrate a remarkable chemical and thermal stability of TCNQ-based 2D MOFs: all the studied systems survive exposure to ambient conditions, with Ni-TCNQ doing so without any significant changes to its atomic-scale structure or chemical state. Thermally, the most stable system is Fe-TCNQ which remains stable above 500 °C, while all the tested MOFs survive heating to 250 °C. Overall, the modular M-TCNQ/graphene system combines the atomic-scale definition required for fundamental studies with the robustness and stability needed for applications, thus we consider it an ideal model for research in single atom catalysis, spintronics or high-density storage media.